Heritage, community and future generations: the transgenerational quest for justice - Davide Grasso (Rivista di Estetica, 2023)
A theory of transgenerational justice ought to be grounded on intuitions shared in the human community. One is parental responsibility, postulating duties between the generating and the generated in a realm of proximity. To achieve greater political abstraction, it is necessary to deny self-sufficiency to such primary transgenerational level, arguing for its structural need to rely on external sources distant in space and time. A critical cross-examining of concepts relevant to justify the leap from proximity to distance follows (community and society, equity and equality, singularity and repetition). The outcome is a notion of ius as object of transgenerational quest, including future generations only at the price of avoiding contractualist understandings of bonds between living and non-living entities.